Senior School Students’ Attitude as Correlate of Physics Achievement: The Empirical Alternative - BADMUS, Olalekan Taofeek; JITA, J Loyiso C. (Journal of Research in Educational Sciences; Vol 13 No 15 (2022): JRES, Volume XIII, Issue 15, Winter 2022, 2022)
In the parlance of literature, phobia is regarded as a major barrier to students learning in many subject areas. However, when students do not possess phobia for a particular subject, they may be indifferent or have the right attitude in such subject. This study investigated students’ attitude as correlate of physics achievement in secondary school. This study indulged ex post facto research of the co-relational type. Eight hundred and fifty-seven (857) respondents formed the sample for the study from three senatorial districts of Kwara State, Nigeria. Attitude Towards Physics Inventory (ATPI) and physics result of respondents in West African Senior School Certificate Examinations (WASSCE) elicited data for the study. Four research questions were raised in this study with corresponding hypotheses. This study found no predictive significance between students’ physics achievement and their attitude towards physics. Moderator variables of score level, gender and school type were also tested in the study.